Pediatric Oculomotor Findings during Monocular Videonystagmography: A Developmental Study - Doettl, Steven M.; Plyler, Patrick N.; McCaslin, Devin L.; Schay, Nancy L. (Journal of the American Academy of Audiology, 2015)
Background: The differential diagnosis of a dizzy patient >4 yrs old is often aided by videonystagmography (VNG) testing to provide a global assessment of peripheral and central vestibular function. Although the value of a VNG evaluation is well-established, it remains unclear if the VNG test battery is as applicable to the pediatric population as it is for adults. Oculomotor testing specifically, as opposed to spontaneous, positional, and caloric testing, is dependent upon neurologic function. Thus, age and corresponding neuromaturation may have a significant effect on oculomotor findings.Purpose: The purpose of this investigation was to describe the effect of age on various tests of oculomotor function during a monocular VNG examination. Specifically, this study systematically characterized the impact of age on saccade tracking, smooth pursuit tracking, and optokinetic (OPK) nystagmus.Research Design: The present study used a prospective, repeated measures design.Study Sample: A total of 62 healthy participants were evaluated. Group 1 consisted of 29 4- to 6-yr-olds. Group 2 consisted of 33 21- to 44-yr-olds. Each participant completed a standard VNG oculomotor test battery including saccades, smooth pursuit, and OPK testing in randomized order using a commercially available system.Data Collection and Analysis: The response metrics saccade latency, accuracy, and speed, smooth pursuit gain, OPK nystagmus gain, speed and asymmetry ratios were collected and analyzed.Results: Significant differences were noted between groups for saccade latency, smooth pursuit gain, and OPK asymmetry ratios. Saccade latency was significantly longer for the pediatric participants compared to the adult participants. Smooth pursuit gain was significantly less for the pediatric participants compared to the adult participants. The pediatric participants also demonstrated increased OPK asymmetry ratios compared to the adult participants.Conclusions: Significant differences were noted between the pediatric and adult participants for saccade latency, smooth pursuit gain, and OPK asymmetry. Saccade latency was significantly longer for the pediatric participants compared to the adult participants. Smooth pursuit gain was significantly less for the pediatric participants compared to the adult participants. The pediatric participants also demonstrated increased OPK asymmetry compared to the adult participants. Caution should be exercised when comparing pediatric test results to adult normative values to avoid “false positive” diagnoses of central vestibular involvement.
Keywords: dizziness; oculomotor; vertigo; vestibular testing; videonystagmography